Predictors of 30‐day and 12‐month mortality in left main stem percutaneous coronary intervention 2016−2020: A study from two UK centers. Issue 4 (14th September 2022) - Carande, Elliott J.; Protty, Majd B.; Verhemel, Sarah; Hussein, Mohammed H.; Raman, Ajay S.; UlHaq, Zia; Bundhoo, Shantu; Cullen, James; Ionescu, Adrian; Choudhury, Anirban; Hussain, Hussain I.; Hailan, Ahmed
Abstract: Introduction: Left main stem percutaneous coronary intervention (LMS‐PCI) is a complex high‐risk procedure which can be performed as an alternative to coronary artery bypass graft (CABG) procedure in surgical turn‐down patients or where there is equipoise in percutaneous versus surgical strategies. Current guidelines suggest that PCI is an appropriate alternative to CABG in patients with unprotected LMS disease and low SYNTAX score. However, "real world" data on outcomes of LMS‐PCI remain limited. This study aims to quantify and determine predictors of mortality following LMS‐PCI. Methods: Using local coronary angioplasty registries from two UK centers, all LMS‐PCI cases were identified from 2016 to 2020. Descriptive statistics and multivariate logistic regressions were used to examine the association between baseline and procedural characteristics with 30‐day and 12‐month mortality. Results: We identified 484 cases of LMS‐PCI between 2016 and 2020. There was a year‐on‐year increase in the number of LMS‐PCI, the highest being in 2020. Covariates associated with higher 30‐day mortality were age (OR 1.07, 95% CI: 1.02−1.12) and shock preprocedure (OR 23.88, 95% CI: 7.90−72.20). Covariates associated with higher 12‐month mortality were age (OR 1.04, 95% CI: 1.01−1.08), acute coronary syndrome (ACS) (OR 2.50, 95% CI: 1.08−5.80), renal disease (OR 5.24, 95% CI: 1.47−18.68), and shock preprocedure (OR 7.93, 95% CI: 3.30−19.05). Overall, 30‐day and 12‐month mortality in this contemporary data set were 9.5% and 16.7%, respectively, with significantly lower rates in elective cases ( p  < 0.01). Conclusions: Older age and cardiogenic shock preprocedure were associated with increased 30‐day mortality after LMS‐PCI. Twelve‐month mortality was associated with older age, ACS presentation, preexisting renal disease, and cardiogenic shock preprocedure.